Preconception risk assessment for thalassaemia, sickle cell disease, cystic fibrosis and Tay-Sachs disease - Hussein, Norita; Weng, Stephen F.; Kai, Joe; Kleijnen, Jos; Qureshi, Nadeem (Wiley, 2015)
Background: Globally, about five per cent of children are born with congenital or genetic disorders. The most common autosomal recessive conditions are thalassaemia, sickle cell disease, cystic fibrosis and Tay-Sachs disease, with higher carrier rates in specific patient populations. Identifying and counselling couples at genetic risk of the conditions before pregnancy enables them to make fully informed reproductive decisions, with some of these choices not being available if genetic counselling is only offered in an antenatal setting. Objectives: To assess the effectiveness of systematic preconception genetic risk assessment to improve reproductive outcomes in women and their partners who are identified as carriers of thalassaemia, sickle cell disease, cystic fibrosis and Tay-Sachs disease in healthcare settings when compared to usual care. Search methods: We searched the Cochrane Cystic Fibrosis and Genetic Disorders Group's Trials Registers. In addition, we searched for all relevant trials from 1970 (or the date at which the database was first available if after 1970) to date using electronic databases (MEDLINE, Embase, CINAHL, PsycINFO), clinical trial databases (National Institutes of Health, Clinical Trials Search portal of the World Health Organization, metaRegister of controlled clinical trials), and hand searching of key journals and conference abstract books from 1998 to date (European Journal of Human Genetics, Genetics in Medicine, Journal of Community Genetics). We also searched the reference lists of relevant articles, reviews and guidelines and also contacted subject experts in the field to request any unpublished or other published trials. Date of latest search of the registers: 25 June 2015. Date of latest search of all other sources: 10 December 2014. Selection criteria: Any randomised or quasi-randomised control trials (published or unpublished) comparing reproductive outcomes of systematic preconception genetic risk assessment for thalassaemia, sickle cell disease, cystic fibrosis and Tay-Sachs disease when compared to usual care. Data collection and analysis: We identified 19 papers, describing 13 unique trials which were potentially eligible for inclusion in the review. However, after assessment, no randomised controlled trials of preconception genetic risk assessment for thalassaemia, sickle cell disease, cystic fibrosis and Tay-Sachs disease were found. Main results: No randomised controlled trials of preconception genetic risk assessment for thalassaemia, sickle cell disease, cystic fibrosis and Tay-Sachs disease were found. Authors' conclusions: As no randomised controlled trials of preconception genetic risk assessment for thalassaemia, sickle cell disease, cystic fibrosis, or Tay-Sachs disease were found for inclusion in this review, the research evidence for current policy recommendations is limited to non-randomised studies. Information from well-designed, adequately powered, randomised trials is desirable in order to make more robust recommendations for practice. However, such trials must also consider the legal, ethical, and cultural barriers to implementation of preconception genetic risk assessment.